Treating idiopathic hypertrophic pyloric stenosis with sequential therapy: A clinical study. (July 2016) - Fan, Jianfeng; Shi, Yingzuo; Cheng, Ming; Zhu, Xiaomin; Wang, Dafeng
Abstract : Aim: The aim of this study was to explore the efficacy and safety of treating idiopathic hypertrophic pyloric stenosis with sequential therapy (ST). Methods: From January 2010 to June 2013, 49 children with idiopathic hypertrophic pyloric stenosis were divided into two groups to accept either atropine ST (ST group, n = 26) or laparoscopic surgery (operation group, n = 23). The remission rate of vomiting, complications, hospital stay and medical expenditure were compared between the two groups. The body weight and the thickness of the pyloric muscle at 6 months after the treatments were also compared. Results: The remission rate of vomiting was lower in the ST group (88.5%; 23/26) than in the operation group (100%, 23/23). The difference in the incidence rate of complications, body weight and pyloric muscle thickness was not statistically significant between the two groups. However, the hospital stay was significantly longer, while the medical expenditure was significantly lower in the ST group than in the operation group. Conclusions: Atropine ST is safe, effective and cost‐effective as compared with operation; however, the efficacy of ST is lower than operation.